# What is the common difference d of the sequence? 9, −8, −25, −42, −59, ... d =

**So, your final answer is -17**

Hope this helps!

## Related Questions

Which ordered pair is a solution of the equation 2x − y = 9 (-4,1) (-2,5) (5,1) (6,-3)

So based on my solution, the correct answer would be the third option: (5,1)

So let us try to plug in the values.

2(5) - 1 = 9

10 -1 = 9

9 = 9

So this is the correct one. Hope this answers your question.

What is the range of the function f(x) = 3x2 + 6x – 9

f(x)=3x^2-6x+1

My solution is:

The domain is all real numbers--there are no restrictions like a square root or variable in the denominator

this is a U shape parabola and you want to find the bottom point, it is at the vertex

x=-b/2a =- (-6) /2 (3) =1

f(1) =3(1)^2 -6(1) +1 =3-6+1 =-2

the minimum is (1, -2)

so the range is all real numbers >= -2

By examining my solution, you could just answer the problem on your own! I hope it helps!

Solve the equation for y 2x+6y=13

2x+6y=13

Next, transfer 2x to the right side and it will look like this:

6y=13-2x

Now, divide both sides by 6, and it will look like this:

y=13-2x

--------

6

So, this is the final answer for y.

Hope this answers your question. Have a great day!

**Answer:**

D

**Step-by-step explanation:**

She showed that f(n) - f(n - 1) was a constant difference.

The definition of an arithmetic sequence is** the difference between consecutive terms is constant, aka common difference.**

How to solve this problem 14-6= 10-6=?

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

Algebraic terms are separated by ______. Choose all that apply. 1)= 2)+ 3)x 4)÷ 5)-

__Answer__

1)=

2)+

5)-

__Explanation__

When letter or numbers are separated by multiplication or division can be combined to make one term.

In an algebra equation, terms are separated by an addition sign, subtraction sign or an equal sign. For example,

3a + 7b = 21.

This equation have 3 terms.

**If ST = 21, SP = 3b – 11, and PT = b + 4, the value of b would be 14.**

I hope my answer has come to your help. God bless and have a nice day ahead!

is as follows

mean=13(.5)=6.5

variance=6.5(.5)=3.25

Pr[fewer than 4]=

Pr[N<=3] Apply the continuity correction

Pr[N<=3.5]~=Pr[Z<3.5-6.5/sqrt(3.25)]=

Pr[Z<-1.66]=0.048457226

I hope my answer has come to your help. God bless and have a nice day ahead!

6 times the square root of 2.25 and then minis 4.23 =

________________

6√(2.25) - 4.23 = ?

__________________

6√(2.25) - 4.23 =

______________________

6*(1.5) - 4.23 =

_______________

9 - 4.23 =

_______________

4.77

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

**1) The answer is: [B]: r = 5 .**

**__________________________**

**Explanation:**

**___________**_______________

Given: 7r − 7 = 2r + 18 ; Round your answer to the nearest tenth, if necessary.

____________________________

Since "r" is the only variable given, let us assume we want to solve for "r" (instead of "x").

___________________________

→ Subtract "2r" from EACH SIDE of the equation; and & add "7" to EACH SIDE of the equation:

_____________

→ 7r − 7 − 2r + 7 = 2r + 18 − 2r + 7 ; to get: → 5r = 25 ;

_____________

→ Now, divide EACH SIDE of the equation by "5"; to isolate "r" on one side of the equation; and to solve for "r" :

______________

→ 5r / 5 = 25 / 5 → r = 5 → which is: "Answer choice: [B]".

_________________

**Let us check our answer, by plugging in "5" for "r" in the original equation:**

_________________

→ 7r − 7 = 2r + 18 ; → 7(5) − 7 =? 2(5) + 18? ;

______________________

→ 35 − 7 =? 10 + 18 ?; → 28 =? 28? Yes!

______________________

**2) The answer is: [D]: x = 2 .**

**_____________**

**Explanation:**

_____________

Given: 2x + 12 = 18 − x ; Solve for "x" (round to nearest tenth, if necessary).

_______________

→ Add "x" to EACH SIDE of the equation, & subtract "12" from EACH SIDE of the equation: → 2x + 12 + x − 12 = 18 − x + x − 12 ;

______________

→ To get: 3x = 6 ; → Divide EACH SIDE of the equation by "3";

to isolate "x" on one side of the equation; and to solve for "x":

_____________

→ 3x / 3 = 6 / 3 ; → x = 2 ; which is: "Answer choice: [D]".

______________

**Let us check our answer, by plugging in "2" for "x" in the original equation:**

________________

→ 2x + 12 = 18 − x ; → 2(2) + 12 =? 18 − 2 ?

________________

→ 4 + 12 =? 18 − 2 ? ; → 16 =? 16? Yes!

________________________________

**3) The answer is: [A]: x = -3 .**

**_____________**

**Explanation:**

________________

Given: 8x − 3 = 15x + 18 ; Solve for "x". Round your answer to the nearest tenth, if necessary.

_________________

→ Subtract "8x" from EACH SIDE of the equation, & add "3" to EACH SIDE of the equation:

_______________

→ 8x − 3 − 8x + 3 = 15x + 18 − 8x + 3 ; to get:

_______________

→ 0 = 7x + 21 ; → Subtract "21" from EACH SIDE of the equation;

_______________

→ 0 − 21 = 7x + 21 − 21 ; to get:

_______________

→ -21 = 7x ; Now divide EACH SIDE of the equation by "7";

to isolate "x" on one side of the equation; & to solve for "x":

_______________

→ = -21 / 7 = 7x / 7 ; → -3 = x ; which is "Answer choice: [A]."

**_________________**

**Let us check our answer, by plugging in "-3" for "x" in the original equation:**

________________

→ 8x − 3 = 15x + 18 ; → 8(-3) − 3 =? 15(-3) + 18 ?;

________________________

→ -24 − 3 =? -45 + 18 ? ; → -27 =? -27? Yes!

**___________________________**

**4) The answer is: [C]: y = 11 .**

**_____________**

**Explanation:**

**____________**

Given: 6y − 6 = 4y + 16 ; Solve for "y"; Round to the nearest tenth, if necessary.

____________

(Note: Since "y" is the only variable given; assume we are to solve for "y" instead of "x").

____________

→ Subtract "4y" from EACH SIDE of the equation, & add "6" to EACH SIDE of the equation; → 6y − 6 − 4y + 6 = 4y + 16 − 4y + 6 ; to get:

_______________

→ 2y = 22 ; Now, divide EACH SIDE of the equation by "2"; to isolate "y" one side of the equation; and to solve for "y" ;

_______________

→ 2y / 2 = 22 / 2 ; → y = 11 → which is "Answer choice: [C]".

**_______________________________**

**Let us check our answer, by plugging in "11" for "y" in the original equation:**

**___________________**

→ 6y − 6 = 4y + 16 ; → 6(11) − 6 =? 4(11) + 16 ?

_______________________

→ 66 − 6 =? 44 + 16 ? → 60 =? 60 ? Yes!

**__________________**

**5) The answer is: [B]: x = -11 .**

**_____________________**

**Explanation:**

**_________________**

Given: 3(x − 4) = 5(x + 2) ; Solve for "x". Round to the nearest tenth, if necessary.

**___________**

**→Note the "distributive property of multiplication":**

**_____________**

**a*(b + c) = ab + ac ; and: a*(b − c) = ab − ac ;**

**_______________**

→ Let us expand EACH SIDE of our given equation.

→Start with the "left-hand side":

____________

3(x − 4) = (3*x) − (3*4) = 3x − 12;

______________________________

→Now let us expand the "right-hand side" of the given equation:

____________

→ 5(x + 2) = (5*x) + (5*2) = 5x + 10 ;

______________

→Now, we can rewrite the original equation:

_______________

→ 3(x − 4) = 5(x + 2) ; by substituting the expanded values for EACH SIDE of the question: → 3x − 12 = 5x + 10 ;

__________________

→ Subtract "3x" from EACH SIDE of the equation; and add "12" to EACH SIDE of the equation: → 3x − 12 − 3x + 12 = 5x + 10 − 3x + 12 ; to get:

________________

→ 0 = 2x + 22; → Now subtract "22" from EACH SIDE of the equation:

______________

→ 0 − 22 = 2x + 22 − 22 ; to get: → -22 = 2x ;

__________

→ Divide EACH SIDE of the equation by "2"; to isolate "x" on one side of the equation; & to solve for "x" ;

_____________

→ -22 / 2 = 2x /2 ; → -11 = x ; which is "Answer choice: [B]".

______________

**Let us check our answer, by plugging in "-11" for "x" in the original equation:**

**___________**

→ 3(x − 4) = 5(x + 2) ; → 3(-11 − 4) =? 5(-11 + 2) ? ;

_______________________

→3(-15) =? 5(-9) ? ; → -45 =? -45 ? Yes!

**_____________________________________________**

**Hope these answers and explanations are helpful. Best of luck!**

Solve for w. 2w=12-4w Simplify your answer as much as possible.

2w=12-4w

Firstly, let's simplify, and divide all terms by 2:

w=6-2w

Now, we add 2w over to the other side:

3w=6

And finally, we divide both sides by 3:

w=2

Hope this helps!

Round 89,891 to the nearest ten-thousands place.

You need to increase this digit because the thousands digit is greater than zero.

The answer is 90,000.

f ( x ) = √( 1 - x²), g ( x ) = - 2

= - 50/3

My = p ∫ x * ( f ( x ) ) dx

My = p ∫ x ( √(1+x²)) dx

Substitution: 1 - x² = u, x dx = - du/2

**M x = - 50/3, M y = 0**

M ≈ 5 * 6.3 ≈ 31.2

x = M y / M = 0 / 31.5 = 0

y = M x / M = -50/3 : 31.5 ≈ - 0.529

The center of mass is

**( 0, -0.529 )**

we have

Combine like terms

therefore

__the answer is the option C__

He combined the terms and incorrectly

## Use our writing service to score better and meet your deadlines

No matter what kind of academic paper you need, it is simple and secure to hire a writer for a price you can afford at StudyHawks. Save more time for yourself.

Find the value of 3x + 2 when 7+ x = 5

x= 5-7

x= -2

3.(-2)+2

-6+2

-4

What is the answer for 5(n-6)-2=2n-5

5n-30-2 = 2n-5

5n - 2n = 30+2-5

3n = 27

n = 27/3

n = 9

**So, your final answer is 9**

Hope this helps!

Is 50 tens 9 ones <,>,= 49 tens 35 ones

## Use our writing service to score better and meet your deadlines

Find all the zeros of the function y=x^3+6x^2+x+6

one more thing X= not real solution

Graph passes through the point (-1, 0).

Therefore, x = -1 and y = 0.

This is the only equation which is true for x = -1 and y = 0.

Therefore, the solution is

Find sinx2, cosx2, and tanx2 from the given information.sin(x) = 513, 0° < x < 90°

K-X=V-W solve for the letter x

Mul -1 X = -(V-W) + K

X = -V + W + K

## Use our writing service to score better and meet your deadlines

**Answer:**

Just took the test!!

**Step-by-step explanation:**

Look at the image down below!!

WILL UPVOTE! Which equation is related to 89 = x + 61? A. x = 150 B. 61 = 89 + x C. x = 28 D. x = 18

y(x) = 8 * 3^x where x = 4:

y(x) = 8 * 3^4 = 8 * 81

y(x) = 648

The Function Rule then being that for every value of x there is one and only one value of y. y is the dependent variable and x is the independent variable.